Impaired Secretion of TNF-α by Monocytes Stimulated With EBV Peptides Associates With Infectious Complications After Kidney Transplantation. Issue 6 (June 2018) - Vallin, Patrice; Désy, Olivier; Béland, Stéphanie; Bouchard-Boivin, François; Houde, Isabelle; De Serres, Sacha A.
Abstract : Background: The successful development of immunosuppressive agents has paradoxically led to an era in which adverse effects of immunosuppression, such as infections and cancer, are now a major concern in solid organ recipients. Nevertheless, the main focus of immune monitoring research remains the identification of rejection. There is currently no clinical tool to assess the net state of immunosuppression or to identify patients at increased risk of infectious complications. Methods: We report a prospective, longitudinal study in which we conducted detailed phenotyping of over 300 peripheral blood mononuclear cell samples from 45 kidney recipients during the first 24 months posttransplant. Patients were classified as cases or controls according to the following events: an opportunistic infection, recurring bacterial infections, or de novo neoplasia. Results: Using a training cohort, an exploratory analysis revealed that the TNFα response to synthetic Epstein-Barr virus peptides by CD14 + CD16 + monocytes was lower in cases. A classifier rule based on 2 or greater consecutive values below a threshold of 73% of TNFα-positive cells provided a sensitivity and specificity of 83%. In the validation cohort, the assay exhibited a sensitivity of 90% and a specificity of 63%. Analysis of IFNγ responses by T cells showed no correlation with the cases' phenotype. The association between overimmunosuppression status and the monocyte response was independent of age, renal function, and immunosuppressive regimen. Conclusions: These data suggest that patients with infectious complications posttransplantation have lower CD14 + CD16 + monocyte responses to Epstein-Barr virus peptides. This assay seems promising to help personalize the immunotherapy. Abstract : A threshold of < 73% TNFα-positive monocytes after stimulation with EBV peptides correlates with over-immunosuppression as defined mostly by BK viremia with sensitivity of 87.5%, specificity of 68%, a positive predictive value of 63.6%, and a negative predictive value of 89.5%. Supplemental digital content is available in the text.